As ordenações Afonsinas e a nobreza portuguesa no século XV : tentativa de construção da sociedade ideal - Lima, Angela Sampaio de Deus (2010)
Considering the "Ordenações Afonsinas" as a Government Institution, this research had as objective understand how they were thought, structured and what kind of behaviors were designed by them to the Portuguese society of the 15th century. They were written during the turn of the Middie Age to tle Modern Age, the "Ordenações Afonsinas" tried to discipline and design the limits of the nobility's power in the presence of the King and the other social categories. They were published in 1446, during the reign of D. Afonso V (1438-1481), they are compound by a collection or code of laws and many legal sources that gathered all the Portugueses legislation in force in that context. With the publishing of the "Ordenações Afonsinas", the laws became equal for all the territory, according this way, it can allowed to comprehend the violations and abuses practiced by the nobility. The Portugueses monarch, through the "Ordenações", broadened his project of politics concentration. ly on the one hand the king searched the power centralization diminishing the nobility's influence, on the other hand, it looked for disciplining it for the benefit of the harmony of its own reign. Through them, it is possible to understand the politics dynamics and its relation to the nobility too, that, although, they revealed contradictory interests, many times, and at the same time, were complementary. Understand how the "Ordenações Afonsinas" were structured and organized, and who such laws were conceived for, is very important to analyze the relation between "society" and "government institution" of the studied period.